New AMH cutoff values for warning of decreased ovarian response based on MCL characteristics in young women: a retrospective study using a propensity score-matching analysis - Jia-Bei Lv; Ying Han; Xin-Yan Wang; Li-Na Yuan; Jun-Rong Diao; Ya-Zhen Fan; Hai-Ning Luo (BMC, 2022)
Abstract Background Menstrual cycle length (MCL) and ovarian response varies widely among women of childbearing age. They are provided with anti-Mu¨llerian hormone (AMH) cutoffs for "normal" and "weakened" ovarian responses, which give an early warning of the onset of decreased ovarian response. Methods This was a retrospective study in women aged 21 to 35 years with MCLs of 21-35 days receiving in vitro fertilization (IVF) treatment at Center for Reproductive Medicine from October 2018 to October 2021. Intergroup variables were balanced using propensity score matching based on age and BMI, and each case patient (patients with MCLs of 21-25 days) was matched with three control patients (patients with MCLs of 26-35 days). A receiver operating characteristic curve was used to calculate the AMH cutoff values. Results We included 135 patients with MCLs of 21-25 days and 405 matched control patients with MCLs of 26-35 days who received IVF treatment. The case group had significantly fewer retrieved oocytes, lower AMH values and higher initial and total Gonadotropin (Gn) levels during controlled ovarian hyperstimulation than the control group. The ovarian response began to decrease when AMH was < 3.5 ng/ml in the case group and < 2.7 ng/ml in the control group. Conclusion In young women with MCLs of 21-35 days, short MCL was negatively correlated with AMH values and the number of oocytes retrieved. In patients with MCLs of 21-25 days and 26-35 days, the AMH cutoff values corresponding to the onset of decreased ovarian response were 3.5 ng/ml and 2.7 ng/ml, respectively.